2019
DOI: 10.28991/cej-2019-03091438
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Fundamental Period of Vibration for Moment Resisting Concrete Frames

Abstract: The determination of fundamental period of vibration for structures is essential to earthquake design. The current codes provide empirical formulas to estimate the approximated fundamental period and these formulas are dependent on building material, height of structure or number of stories. Such a formulation is excessively conservative and unable to account for other parameters such as: length to width ratios, vertical element size and floors area. This study investigated the fundamental periods of mid-rise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…The period is increased by 9 percent to 71% when the opening ratio in the walls is increased [7]. Some in ll wall apertures, such as windows and doorways, alter the in ll wall stiffness and extend the fundamental time period [11].…”
Section: Effect Of In Ll Wallmentioning
confidence: 99%
See 1 more Smart Citation
“…The period is increased by 9 percent to 71% when the opening ratio in the walls is increased [7]. Some in ll wall apertures, such as windows and doorways, alter the in ll wall stiffness and extend the fundamental time period [11].…”
Section: Effect Of In Ll Wallmentioning
confidence: 99%
“…Ahmed 2019 [11]conducted a study by considering varied length-to-width ratios, vertical element size, oor area, and building height, the suggested equation is utilized to predict the time period of momentresisting frames.…”
Section: Prediction Of Fundamental Time Periodmentioning
confidence: 99%
“…Kwon and Kim (2010) investigated the ASCE/SEI 7-05 building period formulae for known resisting systems and concluded that these formulae, in general, predict accurately the lower bound of the fundamental period for low-to medium-rise braced frames and overestimate the fundamental natural period of shear wall buildings. Ahmed et al (2019) determined the fundamental period of mid-rise reinforced concrete moment resisting frames by nonlinear dynamic analysis and compared the results with the period formulae in Eurocode 8, UBC 1997 and ASCE/SEI 7-16. They proposed some equations for calculating the period of vibration by regression analysis of the results.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple fundamental period to building height relations for different seismic intensities were developed by Verderame et al [31] based on modal analyses results. Mohamed et al [32] used applied element method in modeling reinforced concrete buildings and conducted nonlinear dynamic analysis in which the fundamental period was extracted from the time history curve. An equation relates fundamental vibration period to building height, building width to length ratio and column size was developed.…”
Section: Introductionmentioning
confidence: 99%